The necessity of equal protection between employer and employee in the duty of fidelity pertaining to confidential information: a comparative analysis / Muhammad Iqram Zulkifli … [et al.] - Zulkifli, Muhammad Iqram; Khairul Anuar, Khairul Muzhaffar; Saharudin, Izzat Amir; Mohd Rosli, Erin Nadhirah (2013)
Currently the enforcement regarding the law that govern duties between employer and employee is still vague. The vagueness of the law remains an issue as it lead to an unequal protection offered toward both parties which are employer and employee. The conflict can be seen when the employer is unclear to what extent their interest can be guarded and the dilemma of the ex employer to advance their future after the post employment period without being accuse to use their ex employer's confidential information. It can thus be concluded that the sufficiency of implied term in common law pertaining to the duty of fidelity in term of confidential information between employer and employee needed to be review. This study will examine on the sufficiency of the protection pertaining to the duty of good faith and fidelity in terms of confidential information between employer and employee. This study also is to show that there are necessity of equal protecting amongst the employer and employee in this pertaining matter. One of the objectives of this research is to assist the policy maker to draw up a legal framework that could provide the balance in protecting the interest of employer as well as employee with regards to confidential information. In this proposed research, the purpose is to explore the usual practices of employers and employees on the duty of fidelity pertaining to confidential information in the public and private sector through the utilisation of the qualitative research method. The primary sources used in this research are mainly statutes, subsidiary legislations, regulatory frameworks and cases in Malaysia, Singapore, Hong Kong and the United Kingdom. This particular research will run through a comparative analysis by comparing with other jurisdiction where the duty of fidelity pertaining to confidential information which applies on United Kingdom, Singapore and Hong Kong. This research shall help in highlighting the existing laws, the frameworks and the lacunae in the respective jurisdictions such as Malaysia, Singapore, Hong Kong and United Kingdom in order to provide a definite guideline as to develop the law in Malaysia and to promote better practice of the enforcement of the law and work between the employers and employees. This significance of this research will provide suggestions and recommendations, which might be used as a reference to assist the Parliament in enacting better law for the betterment of the public at large. Confidential information plays a very vital role in the survival of an organization and institution. Nevertheless, the falling of this kind of information to the wrong hands shall lead to implications that are detriment to the employer's business. Meanwhile, in the context of confidential information, the duty of fidelity requires that an employee must not use information obtained in the course of their employment to the detriment of the employer's business. However, no such definite framework that governs on what shall be confidential and what is only a mere information. This is because employers tend to overrate the information that they have and restrain the employees from using it, even after they leave the course of employment. Thus, it can be concluded that these are the reasons why there shall be an analysis on the problems and the challenges of protecting the confidential information, be it either in the public or the private sector which will be discussed in the entire chapters of this research.